Avaliação da qualidade dos serviços prestados na Atenção Primária à Saúde de Araguari/MG pelos usuários da Estratégia Saúde da Família - Rodrigues, Murilo Franco (2021)
Public health in Brazil has gone through several phases and has evolved according to the political and economic contexts advocated for each period. The current model was arrived at due to the policies arising from the Federal Constitution of 1988. Thus, Primary Health Care, within the context of SUS, is considered as one of the main strategies for disease prevention, health promotion and longitudinal monitoring of families. Brazilian companies. The services offered by the PHC are made available to the population by the Family Health Strategy Teams. Thus, it is noted the importance of evaluating the services provided by the ESF in the context of Primary Care, as it becomes an important tool for the planning and implementation of public health policies at the federal, regional and municipal levels. The general objective of this study is to analyze the perception of users of the Family Health Strategy in the municipality of Araguari / Mg about the quality of the attributes belonging to Primary Health Care, using the PCATool. For this, the study was carried out in the 22 ESF teams in the city of Araguari registered by the Ministry of Health. The work has a descriptive and quantitative nature. The data collection method adopted was through a questionnaire validated in the Brazilian context, which is the PCATtool Adult version. 404 users of the health services of the 22 UBFs took part in this study. The treatment of the scores obtained in the Pcatool questionnaires was processed by the SPSS software (summer 23), where the results were obtained in an aggregated and also comparative way between the UBSFs. The results obtained showed that the general evaluation of the ESF teams in Araguari / Mg showed a low value (median = 5.927). The best evaluated attributes were the Degree of Affiliation, First Contact Access - Use, Longitudinality and Coordination - Integration of care. The worst evaluations were for the attributes of First Contact Access - Accessibility and Comprehensiveness - Services Provided. The results indicate that corrective actions should be planned based on these assessments, with the purpose of improving the quality of the services provided at the PHC in Araguari / Mg. The municipality must train ESF civil servants within the principles of PHC in order to strengthen health promotion and disease prevention actions with users, thus solving great demands at the basic level of assistance.